2020
DOI: 10.1186/s12865-020-0333-9
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of TNF-α and IFN-γ expression is a common host immune response in a chronically infected mouse model of melioidosis when comparing multiple human strains of Burkholderia pseudomallei

Abstract: Background: Melioidosis is endemic in Southeast Asia and Northern Australia and is caused by the Gram-negative, facultative intracellular pathogen Burkholderia pseudomallei. Diagnosis of melioidosis is often difficult because of the protean clinical presentation of the disease, and it may mimic other diseases, such as tuberculosis. There are many different strains of B. pseudomallei that have been isolated from patients with melioidosis, but it was not clear if they could cause a similar disease in a chronic B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 74 publications
3
13
0
Order By: Relevance
“…This study demonstrated that caseous granulomas are formed during chronic melioidosis, but the response is heterogenous, and also includes non-necrotic granulomas and pyogranulomatous lesions. The severity of the lesion, both microscopically and macroscopically, correlates with the number of bacteria within the lesion, which agrees with more recent studies [ 4 ]. Based on comparisons between laboratory and clinical studies, it is evident that MNGCs are the keystone event of Bpm pathogenesis.…”
Section: Role Of Mngcs In Diseasesupporting
confidence: 92%
See 2 more Smart Citations
“…This study demonstrated that caseous granulomas are formed during chronic melioidosis, but the response is heterogenous, and also includes non-necrotic granulomas and pyogranulomatous lesions. The severity of the lesion, both microscopically and macroscopically, correlates with the number of bacteria within the lesion, which agrees with more recent studies [ 4 ]. Based on comparisons between laboratory and clinical studies, it is evident that MNGCs are the keystone event of Bpm pathogenesis.…”
Section: Role Of Mngcs In Diseasesupporting
confidence: 92%
“…As previously stated, MNGCs have been found in the granuloma-like structures of chronic Bpm infections but mostly on the perimeter of the central necrotic core that houses most of the bacteria [ 4 , 44 ]. This is consistent with the granuloma structure in M. tuberculosis infection where MNGCs are scattered throughout the periphery of the epithelioid cells, foamy macrophages, and lymphocytes.…”
Section: Role Of Mngcs In Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The transient re-activation of persister bacteria would shut down the cytoprotection and manipulation exhibited by Bpm and cause the MNGC to undergo cell death, creating foci of necrosis and inflammation, like the ones seen at the center of the mature granuloma-like lesions of chronic melioidosis patients. As previously stated, MNGCs have been found in the granuloma-like structures of chronic infections but mostly on the perimeter of the central necrotic core that houses most of the bacteria [4,37]. This is consistent with granuloma structure in M. tuberculosis infection where MNGCs are scattered throughout the periphery of the epithelioid cells, foamy macrophages, and lymphocytes.…”
Section: Role Of Mngcs In Diseasesupporting
confidence: 86%
“…These latent infections are generally manifested as symptomatic or asymptomatic, leading to abscesses in the liver, spleen, or lung. The severity of the abscess seems to correlate to the number of bacteria taking refuge within the lesion and have a bias for the spleen and lung; however, liver abscesses have also been observed [4]. These abscesses have been clinically identified as granulomalike lesions and often are confused with extrapulmonary tuberculosis.…”
Section: Introductionmentioning
confidence: 99%